Empirical research on semiotics and visual rhetoric - Danesi, Marcel, 1946- (Information Science Reference, 2018)
"This book sheds light on these images and signs and how the disciplines of semiotics and visual rhetoric can help us decode them in specific ways or else how we can better understand the world in which we live"--